Aspects of beyond the Standard Model string phenomenology - Rosa, J; Joao P T G Rosa (2010)
String theory is currently the best-known candidate for a theory of quantum gravity, having the necessary ingredients to describe all known elementary particles and interactions. It also includes several novel features, arising, for instance, from the additional six compact dimensions required for its internal consistency, making it the natural arena to construct extensions of the Standard Model. In this thesis, we analyze some of the new phenomenological aspects introduced by string theory within the framework of low energy effective theories, focusing on their applications to cosmology, astrophysics and collider experiments. We first consider a particular realization of the brane-world scenario in branonium bound states, showing that the orbital motion of a probe antibrane about a central brane stack leads to a resonant amplification of its world-volume scalar modes. We analyze the cosmological development of this process and also its potential relevance for either dark or baryonic matter generation in the early universe. We then focus on the spectrum of quark and lepton string excitations in warped compactifications, modeled by an effective 5-dimensional Randall- Sundrum throat. Motivated by the observed fermion mass hierarchy, we show that the spin-3/2 Regge excitation of the right-handed top quark is the lightest of such resonances in a significant region of parameter space, possibly lying below the TeV scale, and discuss its potential signatures at the Tevatron and at the LHC. Finally, we study the emission of sub-eV scalar particles by maximally rotating Kerr black holes, motivated by the recent string axiverse proposal. We focus on the spectrum of unstable scalar bound states in the superradiant regime, leading to an exponentially large axion cloud around astrophysical black holes, and analyze two semi-analytical methods for computing the growth rate of this instability, comparing the obtained results with previous analytical and numerical analyses.